2020
DOI: 10.2147/cmar.s240268
|View full text |Cite
|
Sign up to set email alerts
|

<p>Toosendanin Suppresses Glioma Progression Property and Induces Apoptosis by Regulating miR-608/Notch Axis</p>

Abstract: Background: Glioma is one the most common and aggressive primary tumors of adult central nervous system worldwide, which tends to develop dysplasia and metastasis. Recently, toosendanin (TSN) has shown pharmacological effects in several cancers. However, little is known about the underlying mechanism of the effect of TSN on glioma and its relationship between miRNA in glioma. Methods: Cell proliferation, cell cycle, cell apoptosis and cell migration were analyzed by CCK-8 cell viability, flow cytometry, wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Apoptosis is known as a form of programmed cell death, and its inhibition leads to unlimited growth of tumor cells [30]. Previous studies have shown that TSN can induce tumor cell apoptosis [15,23]. These results were consistent with our finding that TSN-induced apoptosis is achieved through the activation of a cascade of reactions including the caspase cascade and increased ratio of Bax/Bcl-2.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Apoptosis is known as a form of programmed cell death, and its inhibition leads to unlimited growth of tumor cells [30]. Previous studies have shown that TSN can induce tumor cell apoptosis [15,23]. These results were consistent with our finding that TSN-induced apoptosis is achieved through the activation of a cascade of reactions including the caspase cascade and increased ratio of Bax/Bcl-2.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have recently shown the anti-tumor effects of TSN on different types of malignant tumors [21]; however, the role of TSN in glioma remains unclear. Studies regarding the anti-glioma role of TSN are limited; however, few have shown that the mechanism involves the p53 and mir-608/notch axis [22,23]. For the first time, we propose the role of TSN in the inhibition of the viability and metastasis of glioma cells through the promotion of induced apoptosis and inhibition of the PI3K/Akt/mTOR pathway.…”
Section: Discussionmentioning
confidence: 81%
“…Apoptosis is known as a form of programmed cell death, and its inhibition leads to unlimited growth of tumor cells [30]. Previous studies have shown that TSN can induce tumor cell apoptosis [15,23]. These results were consistent with our nding that TSN-induced apoptosis is achieved through the activation of a cascade of reactions including the caspase cascade and increased ratio of Bax/Bcl-2.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have recently shown the anti-tumor effects of TSN on different types of malignant tumors [21]; however, the role of TSN in glioma remains unclear. Studies regarding the anti-glioma role of TSN are limited; however, few have shown that the mechanism involves the p53 and mir-608/notch axis [22,23]. For the rst time, we propose the role of TSN in the inhibition of the viability and metastasis of glioma cells through the promotion of induced apoptosis and inhibition of the PI3K/Akt/mTOR pathway.…”
Section: Discussionmentioning
confidence: 86%
“…The results also found that, apart from decreased cyclin D1 and increased p21, the expression of p53, a G1-phase checkpoint-associated protein, increased as well ( Wang et al, 2020b ). In addition, cell cycle arrest also occurred in other tumor cells, such as glioblastoma ( Wang Q. et al, 2020 ) and leukemia ( Ju et al, 2013 ).…”
Section: Biological Activities Of Limonoidsmentioning
confidence: 99%